Spatial Modeling of Coastal Flood Vulnerability Driven by Land Subsidence and Sea Level Rise Based on Altimetry and Geospatial Data - Wahyu Hidayat (Structures, Infrastructure, Planning, Implementation, and Legislation, 2026)
Coastal regions in Indonesia are currently facing unprecedented risks from the convergence of global climatic shifts and localized geological instability. This study investigates the intensifying vulnerability of the Jakarta-Bekasi coastal corridor, highlighting it as a critical zone within the broader context of regional climate adaptation. The objective is to evaluate the synergistic impact of eustatic sea-level rise and aggressive land subsidence on permanent inundation projections through 2030. Utilizing a quantitative geospatial design, the research integrates satellite altimetry from the Sentinel-6 mission with terrestrial geodetic data from 12 Continuous Operating Reference Stations (CORS) across a 12,500-hectare study area. Key variables include vertical land motion rates and sea surface height anomalies, processed through high-resolution Digital Elevation Models (DEMNAS). Results indicate that localized land subsidence, peaking at 11.2 cm per year, is the primary driver of flood risk, rendering Relative Sea Level Rise () significantly more destructive than global eustatic averages. Statistical analysis confirms that subsidence accounts for 82% of the variance in coastal inundation expansion, with critical hotspots in the Penjaringan and Muara Gembong sectors. These findings imply that current coastal defense structures are nearing functional failure due to the rapid erosion of operational freeboards. Consequently, the study concludes that regional resilience necessitates a shift from static engineering to adaptive water management and the implementation of Nature-based Solutions. Future research should prioritize AI-driven predictive modeling and volumetric building load analysis to enhance long-term mitigation strategies.